Multistep flow synthesis of vinyl azides and their use in the copper-catalyzed Huisgen-type cycloaddition under inductive-heating conditions - Kupracz, Lukas; Hartwig, Jan; Wegner, Jens; Ceylan, Sascha; Kirschning, Andreas (Beilstein Journal of Organic Chemistry, 2011)
The multistep flow synthesis of vinyl azides and their application in the synthesis of vinyltriazoles is reported. The synthesis relies on a stable polymer-bound equivalent of iodine azide that serves to carry out 1,2-functionalization of alkenes in a telescope flow protocol. The intermediate 2-iodo azides are subjected to a DBU-mediated polymer-supported elimination step yielding vinyl azides in good yield. The third step involves the formation of vinyl triazoles by a copper-catalyzed Huisgen-"click" cycloaddition. The required heat is generated by electromagnetic induction based on copper. Copper serves both as heatable as well as catalytically active packed-bed material inside the flow reactor.
Keywords: flow reactor; inductive heating; iodine azide; polymer-supported reagents; vinyl azides